Vaccination recommendations and timeliness: The German measles case - Andreas Kucher (Universität Augsburg, Institut für Volkswirtschaftslehre, 2019)
High vaccination rates have a social protection function in addition to individual prevention of infections and diseases. To reach herd immunity thresholds and to protect risk groups, the timeliness of immunization is an important goal for vaccination policy. There is currently no causal evidence of age-appropriate immunization for childhood vaccinations. This research investigates how changing the recommended timeliness of vaccination in childhood affects vaccination status, leaving the number of doses during the primary vaccination unchanged. I analyze an adaption in 2001 that shifts the timeliness two and a half years earlier within the second year of life. Using representative German survey data based on vaccination cards, I investigate a timeliness adaption of the measles primary vaccination in 2001, which changed the scheduled age of the second dose among young children aged 2 to 7 years, and use variation of the implementation across states. For adjusted timeliness of the second measles vaccination, the data imply a significant shift into earlier ages after the policy for the treatment group. In the short run, a difference-in-difference strategy implies causal evidence of the up-to-date vaccination probability at the end of the 7th year of life. Additionally, the adaption induced a significant timeliness effect on the up-to-date level of the first measles dose at the end of the second year of life. This effect can be seen as evidence that individuals, in this case parents, respond to nonbinding vaccination recommendation policies and that timing of vaccination is an important factor for reaching vaccination policy aims.
urn:nbn:de:bvb:384-opus4-710610
Keywords: H75; I12; I18; 330; Childhood immunization; Difference-in-differences; Measles vaccination; Timeliness